Prognostic value of a disease-specific health-related quality score in acute heart failure. (3rd October 2022) - Belkin, M; Wussler, D; Kozhuharov, N; Michou, E; Sabti, Z; Walter, J; Goudev, A; Flores, D; Shresta, S; Menosi Gualandro, D; Pfister, O; Breidthardt, T; et al.
Abstract: Background: Despite the striking therapeutic progress made in the treatment of heart failure (HF), rehospitalization rate and mortality remain a major and often unpredictable problem. Previous studies have shown the prognostic value of Kansas City Cardiomyopathy Questionnaire (KCCQ), a score assessing disease-specific health-related quality of life in stable chronic HF patients. Recently, a large study including 4898 patients with acute HF (AHF) enrolled in China reported the incremental predictive ability of KCCQ for a composite outcome of death and rehospitalization. However, these findings were not yet confirmed. In order to address this unmet need, the aim of this study was to examine the prognostic value of KCCQ in another AHF cohort. Purpose: To validate the prognostic value of the KCCQ in AHF. Methods: Goal-directed AfterLoad Reduction in Acute Congestive Cardiac Decompensation Study (GALACTIC) was a prospective, multicenter (n=10), randomized, interventional controlled trial enrolling adult patients presenting with AHF. KCCQ was assessed shortly after admission. We focused on the prognostic value of the short version KCCQ-12, explored the association with the composite of all-cause mortality and AHF rehospitalization within 30- and 180-day follow-up and compared it to the original score. Patients were grouped into quartiles according their KCCQ: high-risk (0–<25), moderate- to high-risk (25–<50), low- to moderate-risk (50–<75) and low-risk group (75–100). Cumulative incidence of assessed endpoints was displayed in Kaplan-Meier curves. Covariate adjustments were made using Cox regression. Prognostic accuracy over N-terminal pro-B-type natriuretic peptide (NT-proBNP) was evaluated by time-dependent area under the curve. Results: Among 781 patients, 419 (median age 78, 35% female, 32% new onset of HF) had a complete set of variables to calculate KCCQ. Follow-up was available in all patients up to 180 days. 29 (7%) and 122 (29%) patients died or were rehospitalized for AHF within 30- and 180-days, respectively. Median KCCQ-12 was 37.5 with 25% of patients attaining the high- and 8% the low-risk group. After adjustment, each 10-point decrease in the KCCQ was associated with a 10% increase in 180-day risk regardless of new onset or acute decompensated chronic HF, age, sex, comorbidities, systolic blood pressure, creatinine, NT-proBNP and sodium levels. The prognostic ability for a 30-day risk was not significant. Using the same adjustments, a 10-point decrease in the original KCCQ was significant for a 20% and a 11% increase in risk for the short- and long-term composite outcome. The prognostic accuracy of KCCQ was comparable to NT-proBNP. Conclusions: Health status, measured by the KCCQ-12 among patients with AHF, is significantly associated with a long-term composite outcome of all-cause mortality and AHF rehospitalization. The original KCCQ overall score is an independent predictor for both, the 30- and 180-day composite outcome. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Union, the Swiss National Science Foundation